Inhibition of Allograft Inflammatory Factor-1 in Dendritic Cells Restrains CD4+ T Cell Effector Responses and Induces CD25+Foxp3+ T Regulatory Subsets - Elizondo, Diana M.; Andargie, Temesgen E.; Yang, Dazhi; Kacsinta, Apollo D.; Lipscomb, Michael W. (Frontiers in Immunology, 2017)
Allograft Inflammatory Factor-1 (AIF1) is a cytoplasmic scaffold protein shown to influence immune responses in macrophages and microglial cells. The protein contains Ca2+ binding EF-hand and PDZ interaction domains important for mediating intracellular signaling complexes. This study now reports that AIF1 is expressed in CD11c+ dendritic cells (DC) and silencing of expression restrains induction of antigen-specific CD4+ T cell effector responses. AIF1 knockdown in murine DC resulted in impaired T cell proliferation and skewed polarization away from T helper type 1 and 17 fates. In turn, there was a parallel expansion of IL-10-producing and CD25+ Foxp3+ T regulatory subsets. These studies are the first to demonstrate that AIF1 expression in DC serves as a potent governor of cognate T cell responses and presents a novel target for engineering tolerogenic DC-based immunotherapies.